The Role of Entrepreneurial Human Capital as a Driver of Endogenous Economic Growth - Isaac Ehrlich; Dunli Li; Zhiqiang Liu (Institute of Labor Economics (IZA), 2017)
We model investment in entrepreneurial human capital (EHC) – the representative enterprise's share of production capacity allocated to investment in innovative industrial and commercial knowledge – as a distinct channel through which firm-specific human capital drives endogenous growth. Our model suggests that institutional factors supporting free markets for goods and ideas, and higher educational attainments of entrepreneurs and workers, enhance endogenous economic growth by augmenting the efficiency of investment in EHC rather than exclusively by themselves. We test these implications using data from Global Entrepreneurship Monitor's Adult Population Survey of 63 countries over 2002–2010 and find robust support for these hypotheses.
Keywords: L26; O31; O43; 330; innovation; entrepreneurship; the market for ideas; human capital; endogenous growth